Prudent Banks and Creative Mimics: Can We Tell the Difference? - Andrew Powell; Marcus Miller; Antonia Maier (Inter-American Development Bank (IDB), 2011)
The recent financial crisis has forced a rethink of banking regulation and supervision and the role of financial innovation. This paper develops a model where prudent banks may signal their type through high capital ratios. Capital regulation may ensure separation in equilibrium, but deposit insurance will tend to increase the level of capital required. If supervision detects risky behavior ex ante then it is complementary to capital regulation. However, financial innovation may erode supervisors ability to detect risk and capital levels should then be higher. Regulators, however, may not be aware their capacities have been undermined. The paper argues for a four-prong policy response with higher bank capital ratios, enhanced supervision, limits to the use of complex financial instruments and Cocos. The results may support the institutional arrangements proposed recently in the United Kingdom.
Keywords: D82; G21; G38; L51; 330